THE EFFECTIVENESS OF THE PRIORITY VILLAGE PROGRAM FOR STUNTING PREVENTION IN CISAAT SUB- DISTRICT, SUKABUMI REGENCY - Syifa Rizqia Zulfa; Tuah Nur; Rizki Hegia Sampurna (DIA: Jurnal Administrasi Publik, 2025)
This study aims to examine the effectiveness of the priority village program for preventing stunting in Cisaat Sub-District, Sukabumi Regency. The urgency of this study is driven by the lack of public awareness about the importance of avoiding stunting, inefficiencies in aid distribution, and the shortage of posyandu (integrated health service posts) supervisors to regularly monitor the growth of toddlers. The research method used is descriptive qualitative with a snowball sampling technique and six informants. The result of this research is that the priority village program for stunting prevention has not been maximally implemented, due to the inability to conduct examinations by stunting experts, lack of human resources, inadequate facilities and infrastructure, and low public understanding of the importance of stunting prevention. The study recommends the need for training and capacity building for health workers, ensuring the availability of facilities and infrastructure, increasing the number of human resources for comprehensive and effective monitoring, and enhancing communication and coordination among all parties. Innovative approaches in community outreach are also required to raise awareness about the importance of stunting prevention.